Moderated Mediation Effect of Feedback Seeking Behavior and Goal Commitment on the relationship between Proactive Personalities and Sales Performance of Insurance Sales Agents in Mombasa, Kenya - Zippy Mukami Njagi; Charles Lagat; Michael Korir (European Scientific Journal, ESJ, 2019)
The purpose of this study was to examine the Moderated Mediation effect of Feedback seeking behavior and Goal Commitment on the indirect relationship between Proactive personalities and Sales performance. The study adapted explanatory research design targeting 448 insurance Sales Agents in Mombasa County, Kenya. Using self-administered questionnaires, reliability test of the research instrument was done by the use of Cronbach’s alpha. The Pearson correlation and conditional process analysis, model 4 and model 58 was used to analyze the data and to test each of the hypotheses. The findings of the study confirm a positive effect of Proactive personalities on Sales performance and Goal Commitment. Goal Commitment was also found to positively affect Sales performance. Furthermore, the result confirms the Mediating effect of Goal Commitment on the relationship between Proactive personalities and Sales performance. The study also confirms that Feedback seeking behavior Moderates the relationship between Proactive personalities and Goal Commitment but does not moderate the relationship between Proactive personalities and Sales performance. Lastly the finding confirms that Feedback seeking behavior Moderates the indirect relationship between Proactive personalities and Sales performance via Goal Commitment. Managers and policymakers should formulate policies and strategies which nurture proactive behaviour among sales people by seeking feedback of their performance as they pursue the individual desired and organization’s set goals.